1998
DOI: 10.1046/j.1460-9568.1998.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal and nuclear localization of myelin oligodendrocytic basic protein isoforms

Abstract: The recently described single copy myelin-associated oligodendrocytic basic protein (Mobp) gene is expressed exclusively in the central nervous system (CNS). The gene encodes a family of small highly basic polypeptides with predicted amino acid lengths of 69, 71, 81, 99 and 170, all of which share a 68 residue amino terminal. Here we report on the subcellular distribution of two of these polypeptides termed MOBP81 and MOBP170 in transiently transfected Cos7 cells using an antibody raised against a region commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…In contrast to MBP, which is very abundant in the membrane sheets (Aggarwal et al, 2011), MOBP appeared to be more restricted to the oligodendroglial cytoplasm and larger processes (Fig. 1F), supporting previous observations (Montague et al, 1998).…”
Section: Mobp Mrna and Protein Levels During Oligodendrocyte Differensupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast to MBP, which is very abundant in the membrane sheets (Aggarwal et al, 2011), MOBP appeared to be more restricted to the oligodendroglial cytoplasm and larger processes (Fig. 1F), supporting previous observations (Montague et al, 1998).…”
Section: Mobp Mrna and Protein Levels During Oligodendrocyte Differensupporting
confidence: 90%
“…As oligodendrocytes tend to extend, spread and retract their processes, MOBP could also stabilize newly formed, lengthened or widened processes while counteracting their retraction. Interestingly, an association of MOBP with microtubules has been observed in cultured oligodendrocytes (Montague et al, 1998), and, here, we show a significant colocalization of α-tubulin with MOBP, of ∼58.3%, in primary oligodendrocytes at 5 DIV when the protein synthesis rate of MOBP appears to be strongly enhanced. It is hence likely that our observed changes in morphological differentiation after the manipulation of MOBP levels are at least in part mediated by the interaction of MOBP with the microtubular network.…”
Section: Mobp and Oligodendroglial Morphological Differentiationsupporting
confidence: 72%
“…6I). Following guidelines we previously described for Nocodzole treatment of Cos7 transfectants [34] we found that OECs exposed to 30 μM Nocodazole for 3 hrs lead to depolymerisation of the microtubular network as evidenced by the breakdown of the characteristic trebecular staining pattern in the vast majority of the treated cells (Fig. 6J).…”
Section: Resultssupporting
confidence: 54%
“…Immunocytochemistry was performed as described (Montague et al, 1998;Yan and Rivkees, 2002). To detect surface antigens, cultures were washed twice with L-15 medium.…”
Section: Immunocytochemistrymentioning
confidence: 99%